2016
DOI: 10.1016/j.meegid.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Type-specific PCR assays for Babesia bovis msa-1 genotypes in Asia: Revisiting the genetic diversity in Sri Lanka, Mongolia, and Vietnam

Abstract: Babesia bovis is the most virulent Babesia organism, resulting in a high mortality rate in cattle. The genetic diversity of B. bovis merozoite surface antigens (MSAs), such as MSA-1, MSA-2b, and MSA-2c, might be linked to altered immune profiles in the host animals. The present study aimed to develop type-specific PCR assays for Asian msa-1 genotypes, thereby re-analyzing the genetic diversity of msa-1 in Sri Lanka, Mongolia, and Vietnam. Specific primers were designed for nine Asian msa-1 genotypes, which had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Cattle, as well as buffaloes, have been screened with highly sensitive PCR assays to detect persistently infected animals in order to genetically characterize the Merozoite Surface Antigen (MSA-1) diversity in Babesia bovis populations present in cattle premises from Mexico [20], Thailand, Brazil and Ghana [21], Vietnam [22], Thailand [23], Sri Lanka, Mongolia and Vietnam [24].…”
Section: Introductionmentioning
confidence: 99%
“…Cattle, as well as buffaloes, have been screened with highly sensitive PCR assays to detect persistently infected animals in order to genetically characterize the Merozoite Surface Antigen (MSA-1) diversity in Babesia bovis populations present in cattle premises from Mexico [20], Thailand, Brazil and Ghana [21], Vietnam [22], Thailand [23], Sri Lanka, Mongolia and Vietnam [24].…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, anaplasmosis has been investigated only recently, primarily using morphological and serological approaches with few reports of molecular identification [1416]. A serological study conducted using the Svanovir ® A. marginale -Ab ELISA kit (SVANOVA Biotech AB, Uppsala, Sweden), revealed 28% of blood samples from lactating cows in northern Vietnam to be positive for specific antibody against A. marginale [15].…”
mentioning
confidence: 99%
“…In other studies, Anaplasma spp. were suspected in animal samples from southern and central Vietnam [14,16]. There remains a need for accurate species identification for better molecular taxonomic understanding of the infections by Anaplasma spp.…”
mentioning
confidence: 99%
“…Antigenic polymorphism has been applied as a strategy by most protozoan parasites to escape the immune response of mammalian hosts, and it is a major obstacle preventing the development of effective vaccines against these parasites [7]. In our present study, analysis of the genetic relationships of B. bovis MSA-1, MSA-2b and MSA-2c of Chinese isolates, with respect to almost all available related sequences deposited in the GenBank database (including Mongolia, Vietnam, Philippines, Thailand, Israel, Vietnam, Sri Lanka, Mexico, Argentina, Brazil, Japan and USA) was conducted [7,12,[18][19][20][21][22][23][24]26,30,31]. Phylogenetic analysis showed that the MSA-1 amino acid sequences had a wide distribution in four clades.…”
Section: Discussionmentioning
confidence: 99%